Pengaruh Strategi Promosi Media Sosial terhadap Keputusan Pembelian N'pure yang Dimediasi Word Of Mouth Marketing - Stefannie, Stefannie; Rusdi, Farid (Kiwari, 2024)
This study aims to find out several things, namely 1. What is the impact or influence of promotion strategies using social media channels on purchasing decisions for the N'Pure brand, Tarumanagara University 2. The influence of social media promotion strategies on the WOM (Word of Mouth) strategy for N'Pure products among Tarumanegara University students 3. The impact or effect of the WOM (Word of Mouth) strategy on purchasing decisions for Tarumanagara University students. This research uses survey and illustration methods in this research using purposeful sampling50. In collecting information, this study used a questionnaire that was tested for validity, reliability, and significance with the T-test. This research produced some information, namely: 1. Promotion has a positive effect on the purchasing decision strategy for N'Pure products through social media. This is evidenced by the T-count of 7.544 and a significance value of 0.000 which is less than 0.05. 2. The positive impact of the social media promotion strategy on word of mouth on the decision of N'pure product buyers as evidenced by the T count of 5.917 with a significant value of 0.000 less than 0.05. Penelitian ini dilakukan untuk mengetahui dampak atau pengaruh strategi promosi menggunakan saluran media sosial terhadap keputusan pembelian brand N’Pure Universitas Tarumanagara, dan pengaruh strategi promosi media sosial terhadap strategi WOM (Word of Mouth) produk N’Pure di kalangan mahasiswa Universitas Tarumanagara, serta dampak strategi WOM (Word of Mouth) terhadap keputusan pembelian pada mahasiswa Universitas Tarumanagara. Riset ini menggunakan metode survei dan ilustrasi dalam riset ini menggunakan purposeful sampling50. Dalam mengumpulkan informasi, penelitian ini memakai kuesioner yang diuji validitas, reliabilitas, serta signifikansi dengan Uji-T. Dalam riset ini menghasilkan beberapa informasi yaitu, promosi berpengaruh positif terhadap strategi keputusan pembelian produk N'Pure melalui media sosial. Hal tersebut dibuktikan dengan T-hitung sebesar 7,544 dan nilai signifikansi 0,000 lebih kecil dari 0,05. Lalu, dampak positif pada strategi promosi media sosial terhadap word of mouth terhadap keputusan pembeli produk N'pure yang dibuktikan dari T hitung sebesar 5,917 dengan nilai signifikan 0,000 lebih kecil 0,05.